1997
DOI: 10.1021/jm960319n
|View full text |Cite
|
Sign up to set email alerts
|

Probes for Narcotic Receptor Mediated Phenomena. 23. Synthesis, Opioid Receptor Binding, and Bioassay of the Highly Selective δ Agonist (+)-4-[(αR)-α-((2S,5R)-4-Allyl-2,5-dimethyl-1-piperazinyl)-3-methoxybenzyl]- N,N-diethylbenzamide (SNC 80) and Related Novel Nonpeptide δ Opioid Receptor Ligands

Abstract: The highly selective delta (delta) opioid receptor agonist SNC 80 [(+)-4- [(alpha R)-alpha-((2S,5R)-4-allyl-2,5-dimethyl-1-piperazinyl)-3-methoxybenzyl]-N ,N- diethylbenzamide, (+)-21] and novel optically pure derivatives were synthesized from the enantiomers of 1-allyl-trans-2,5-dimethylpiperazine (2). The piperazine (+/-)-2 was synthesized, and its enantiomers were obtained on a multigram scale in > 99% optical purity by optical resolution of the racemate with the camphoric acids. The absolute configuration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 30 publications
8
65
0
Order By: Relevance
“…Although SNC80 produced similar effects to SNC162 in ex vivo studies, this compound was more efficacious in behavioral studies, potentially because it was metabolized to the more active SNC86 product. Consistent with previous in vitro studies (Knapp et al, 1996;Calderon et al, 1997), the present findings confirm that the 3-position of SNC80 alters efficacies and potencies in behavioral studies in Sprague-Dawley rats. In addition, these potency and efficacy differences were observed in the forced swim test, suggesting that this behavioral assay can be used to evaluate and to compare efficacy differences among drugs and possibly drug classes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although SNC80 produced similar effects to SNC162 in ex vivo studies, this compound was more efficacious in behavioral studies, potentially because it was metabolized to the more active SNC86 product. Consistent with previous in vitro studies (Knapp et al, 1996;Calderon et al, 1997), the present findings confirm that the 3-position of SNC80 alters efficacies and potencies in behavioral studies in Sprague-Dawley rats. In addition, these potency and efficacy differences were observed in the forced swim test, suggesting that this behavioral assay can be used to evaluate and to compare efficacy differences among drugs and possibly drug classes.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were confirmed in studies in which SNC86 had high affinity for the ␦-opioid receptor (IC 50 ϭ 1.49 nM) in rat brain membranes; but again, this compound was the least selective with a /␦ ratio for inhibition of radioligand ([ ]-enkephalin) binding of 6.5 (Calderon et al, 1997). These studies also demonstrated that SNC80 was less potent (IC 50 ϭ 2.88 nM) but was approximately 130-fold more selective for the ␦-opioid receptor than SNC86.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Some reports indicate peptidic delta agonists elicit dopamine overflow exclusively in the caudate-putamen (Lubetzki et al, 1982;Petit et al, 1986) or the nucleus accumbens (Spanagel et al, 1990;Manzanares et al, 1993), while other reports fail to demonstrate an effect of DPDPE in either area (Mulder et al, 1989;Pentney and Gratton, 1991). These discrepancies could be due to the lack of delta opioid selectivity of DPDPE which produces mu opioid receptor-mediated antinoception in delta opioid knockout mice (Scherrer et al, 2004), whereas SNC80 is greater than 800-fold selective for the delta opioid receptor (Calderon et al, 1997). Indeed, SNC80 failed to induce increases in extracellular dopamine in either the nucleus accumbens or caudate-putamen as measured by in vivo microdialysis at doses that elicited locomotor stimulation and condition placepreference Spina et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…for peptides and peripheral for nonpeptides) or to the pharmacological differences between ␦-opioid agonists. For example, the nonpeptide SNC80 has a lower K i (approximately 8-fold) for the ␦-opioid receptor and is more efficacious than the peptide DPDPE, even though these compounds have similar selectivities for the ␦-over the -opioid receptor (Calderon et al, 1997;Clark et al, 1997). However, no studies have directly explored these differences in vivo.…”
mentioning
confidence: 99%